Evaluation of the mandibular arch in patients with impacted permanent lower canines - Jain Shikha; Agrawal Mamta; Jain Sachin; Jain Shweta (Sciendo, 2015)
To determine the features of the mandibular dental arch in subjects presenting with impacted permanent lower canines.